A Comparative Study of the Central Administration Budget Preparation Process in Turkey and Sweden - (:unkn) unknown (IGI GLOBAL, 2017)
Sweden was one of the countries among the OECD states yielding maximum budget surplus at the end of 1980s and became one of the countries yielding maximum budget deficits in the first years of the 1990s. The budget deficit almost doubled in five years. During that period, the government decided the most important reason of the budget deficits was the budget process itself and commenced studies to reform the budget process and enhance its consistency and reliability. Basic steps were taken to grant budget surplus for whole public sector, to set an allowance cap for whole public sector and create equivalent budget structure for all municipalities and a series of studies were conducted. In this study, the stage of the budget preparation process in Turkey and Sweden will be reviewed and compared to the budget preparation process in Sweden with the budget preparation process in Turkey.